The Christmas wedding guest [large type] - Mallery, Susan (Mallery, Susan. Wishing Tree, 2021)
"The Somerville sisters believe in love, but they've lost faith it will happen for them. Reggie hasn't been home since the end of the world's shortest engagement. When her parents decide to renew their vows, she buffs up her twinkle to help with the Christmas wedding. Unexpectedly, Toby, her first love, is back too, and the spark between them shines as brightly as ever. Done waiting for the one, Dena is pregnant and on her own. Then a gorgeous songwriter checks in to a room at her inn. But Dena is afraid to believe that a rock star could fall for a girl like her. As the Christmas wedding draws closer, these two sisters just might unwrap the most treasured gift of all--love"--